“Medea” in the Greek Courtroom: Contesting Insanity among Jurists, Psychiatrists and the Public - Avdela, Efi (The Historical Review/La Revue Historique, 2022)
This article focuses on the case of the young American woman who killed her three children in 1961 in Athens, attempted to commit suicide and was widely referred to as the “Medea of Kalamaki”. Its goal is to discuss the difficulties that psychiatrists faced in Greek courts to establish themselves as experts on matters pertaining to the mental condition of homicide offenders, and the constant calling into question of their expertise by the judiciary and the press alike. At the same time, the article argues that in the particular circumstances of 1960s Greece, press crime narratives brought forward a third factor involved in the controversy between the judiciary and the psychiatrists, namely “public opinion”, testifying to an “enlarged publicity”. Jane Brown’s two trials attest to the prevalence in both the judiciary and the press of the “Medea narrative” that refuted psychiatric diagnoses of diminished or even a total lack of liability for her acts.